Effective management of intractable neuropathic pain using an intrathecal morphine pump in a patient with acute transverse myelitis - Wu WT (Dove Medical Press, 2013)
Wei-Ting Wu,1 Yu-Hui Huang,2,3 Der-Cherng Chen,4 Yu-Hsuan Huang,1 Li-Wei Chou1,5 1Department of Physical Medicine and Rehabilitation, China Medical University Hospital, Taichung, Taiwan; 2School of Medicine, Chung Shan Medical University, Taichung, Taiwan; 3Department of Physical Medicine and Rehabilitation, Chung Shan Medical University Hospital, Taichung, Taiwan; 4Center of Neuropsychiatry, Department of Neurosurgery, China Medical University Hospital, Taichung, Taiwan, 5School of Chinese Medicine, College of Chinese Medicine, China Medical University, Taichung, TaiwanAbstract: Transverse myelitis is a rare inflammatory myelopathy characterized by loss of motor and sensory function below the affected level of the spinal cord, and causes neurogenic bowel and bladder. Occasionally, it also causes neuropathic pain with spasticity. Traditional therapies for neuropathic pain are multiple, including multimodal analgesic regimens, antiepileptic or antidepressant medications, opioids, sympathetic blocks, and spinal cord stimulation. Persistent neuropathic pain can cause emotional distress by affecting sleep, work, recreation, and emotional well-being. Here we report the case of a patient suffering from intractable neuropathic pain following acute transverse myelitis that was not relieved by combinations of nonsteroidal anti-inflammatory, antiepileptic, antidepressant, and opioid medications, or by acupuncture. Implantation of an intrathecal morphine pump controlled the pain successfully without side effects, and enabled the patient to embark on intensive rehabilitation. The patient's muscle strength has improved significantly and the patient may soon be able to use a walker with minimal assistance.Keywords: intrathecal morphine pump, neuropathic pain, rehabilitation, transverse myelitis